Morphological reduplication in Jordanian Arabic: form and function - Khaled H. Abu-Abbas; Amal R. Alomari (Cogent Arts & Humanities)
This study investigates the phenomenon of morphological reduplication in Jordanian Arabic in light of morphological doubling theory, offering an extensive examination of this type of reduplication in terms of form and function. Data is collected through observation of native speakers on Facebook, local television series, and in face to face daily interaction with people. Morphological reduplication is categorized as involving either the doubling of a semantically empty stem to create a morpheme, or the doubling of a monosyllabic morpheme to achieve specific pragmatic functions. The findings reveal that reduplication is an active and highly productive process in Jordanian Arabic, shedding light on its prominent role in language use and communication. This study not only contributes to a deeper understanding of the typological aspects of morphological reduplication, but also provides valuable insights into the specific characteristics of reduplication in Jordanian Arabic.